Taxonomic remarks on Genista salzmannii group (Fabaceae) in Sardinia and Corsica - Bacchetta, Gianluigi; Brullo, Salvatore; Feoli Chiapella, Laura; Cusma Velari, Tiziana; Fenu, Giuseppe; Giusso Del Galdo, Gianpietro (Phytotaxa, 2020)
A revision of the taxa belonging to the Genista salzmannii group of sect. Erinacoides (Cytiseae, Fabaceae) occurring in Sardinia and Corsica is carried out. The study, based on literature, herbarium materials and field investigations, allowed the recognition of several taxa, such as G. desoleana Valsecchi subsp. desoleana and subsp. martellii subsp. nov., Genista nuragica sp. nov., G. pichisermolliana Valsecchi, G. salzmannii Candolle de subsp. salzmannii, subsp. lobelioides (Gamisans) comb. et stat. nov. and subsp. limbarae subsp. nov. Taxonomical, nomenclatural, karyological, ecological and chorological remarks are provided for each taxa, as well as a detailed iconographies and SEM micrographs of seed testa. An analytical key of all examined taxa is also provided.